IMPACT ON AGING AND AGE-ASSOCIATED DISEASES WITH SPECIAL REFERENCE TO FOOD AND NUTRITION - K.Chitra Devi, S.Bhuvaneswari, G.Subashini, Prabhu Manickam Natarajan, G.Priya Gouri, G. Pooja Jain (Chelonian Research Foundation, 2023)
Senescence is characterized by various physiological changes, all of which have a contrasting effect on the health and lifestyle of the elderly. With advancing age, the significance of nutrition increases. It exerts a significant impact on the quality of life, encompassing both physical and mental well-being. The elderly population experiences a decline in food intake as a result of biological changes. This decrease in food intake can lead to nutritional deficiencies, which are the main cause of different chronic diseases and declining health associated with aging. Intervention can be employed to tackle the persistent condition of dietary insufficiency and malnutrition. This article provides an overview of the relationship between oral health and nutritional status in the elderly, with the aim of promoting a healthy lifestyle in this population. Keywords: geriatric, nutrition, aging, nutritional analysis.